DETERMINAN PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Novitasari , Ni Luh Gde; Widhiastuti, Ni Luh Putu; Kadek Juli Artha (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
This study aims to examine and obtain empirical evidence of the effect of profitability, leverage, public ownership, institutional ownership, managerial ownership, and company status on the disclosure of the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The population of the data in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020 with a total of 179 companies. The sample in this study were 118 companies with a total of 354 companies observed. Sample selection was done by purposive sampling method. The data analysis technique used in this research is multiple regression analysis. The results of this study indicate that the variables of profitability, public ownership, institutional ownership, and company status have a positive effect on financial statement disclosure, while leverage and managerial ownership have no effect on financial statement disclosure.